Principle understanding towards synthesizing Fe/N decorated carbon catalysts with pyridinic-N enriched and agglomeration-free features for lithium–oxygen batteries. Issue 7 (22nd January 2020) - Zhang, Gangning; Zhang, Li; Zhao, Shangqian; Lu, Shigang; Lu, Yan; Sun, Haobo; Wang, Lve
Abstract : Synthesizing a pyridinic-N enriched and agglomeration-free Fe/N-decorated carbon catalyst for lithium–oxygen batteries. Abstract : Metal-N-decorated carbon catalysts are cheap and effective alternatives for replacing the high-priced Pt-based ones in activating the reduction of oxygen for metal–air or fuel cells. The preparation of such heterogeneous catalysts often requires complex synthesis processes, including harsh acid treatment, secondary pyrolysis processes, etching, etc., to make the heteroatoms evenly dispersed in the carbon substrates to obtain enhanced activities. Through combined experimental characterizations, we found that by precise control of the precursors added, a Fe/N uniformly distributed, agglomeration-free Fe/N decorated Super-P carbon material (FNDSP) can be easily obtained by a one-pot synthesis process with distinctly higher pyridinic-N content and elevated catalytic activity. An insight into this phenomenon was carefully demonstrated and also verified in Li–O2 batteries, which delivered a high discharging platform of 2.85 V and can be fully discharged with a capacity of 5811.5 mA h gcarbon+catalyst −1 at the cut-off voltage of 2.5 V by the low-cost Super-P modified catalyst.